Paciente masculino de 48 años de edad con neumonía nosocomial. - Mayorga Castillo, Juan Andrés (2021)
In-hospital or in-hospital pneumonia is considered to be the second largest nosocomial infection, occurring in 4 to 7 cases per 1,000 discharges. Due to their main morbidity and mortality, the pathogenic characteristics of the causative microorganisms are not the same as those of community-acquired pneumonia, hospital pneumonia, and pneumonia related to mechanical ventilation, which constitute a subgroup of respiratory infections within the respiratory system. . Since nosocomial pneumonia is considered one of the 10 most common causes of death in hospitalized patients, research on this topic is very important, so it is necessary to explain the factors and antecedents that affect nosocomial pneumonia infection and its factors risk for adult patients, Necessary precautions are to avoid many situations. The purpose of this work is to determine the factors and antecedents that influence nosocomial pneumonia infection in a 48-year-old patient. It is possible to demonstrate that the health of patients can be improved by combining diagnostic criteria and the correct process of medication and respiratory physiotherapy techniques. It should be noted that there is no measure to completely eradicate these respiratory infections, but there are a number of resources that can help us identify this disease, and a number of preventive measures can be taken to reduce the risk of contracting these diseases.